Manpower Planning; Basic Concepts - الطبولي أبو القاسم (Dirasat in Economics and Business, 1980)
This paper sheds some lights on the role of manpower planning and its effects on the development of the economy. Manpower is a basic factor among the factors of production since labor force represents a very important role in the production process beside other factors of production such as machines and raw materials. Manpower, therefore, is very important to economic development. We may define manpower planning as the work to balance the supply of and demand for manpower. Manpower planning consists of: l . Determining the size and the structure of labor force available. That is what we call the supply side. 2. Determining the size and the structure of the labor force required. This is what we call the demand size. 3. Closing the gap between the demand side and the supply side. This can be done on the macro level for the economy as a whole as well as on the micro level such as a firm. The most important thingis to have a plan for improving and developing methods for manpower planning especially on the micro level since the firms are the basic unit for planning. The firms with efficient manpower planning will be more efficient in producing goods and services.